Implementing and developing Islamic law internationally: challenges in the modern age - Sujono, Imam (Journal of Modern Islamic Studies and Civilization, 2023)
The implementation of Islamic law at the international level faces a variety of complex challenges that include legal, political, social and cultural dimensions. One of the main challenges is the diversity of interpretations of Islamic law in different Muslim countries. Differences in schools of thought, local traditions, and state policies create gaps in the application of the law, which makes it difficult to establish uniform Islamic legal standards globally. Apart from that, the integration of Islamic law into the international legal system which is dominated by secular law is also an obstacle. The current international legal system places greater emphasis on universal principles which sometimes conflict with provisions in Islamic law, especially on issues such as human rights, gender equality and religious freedom. Another challenge arises from the geopolitical aspect, where countries with different political and economic interests are often reluctant to agree on a global Islamic legal framework. In addition, negative perceptions of Islamic law among non-Muslim communities also play a role in hindering constructive dialogue between civilizations. This condition is exacerbated by the stigma of terrorism which is often associated with the extreme application of Islamic law. Therefore, efforts are needed for cross-cultural dialogue and reform of Islamic law that is inclusive and adaptive to the global context without ignoring the basic principles of religion.